The Effect of Assertive Discipline on Early-Aged Children’s Gadget Addiction - Muniroh Munawar; Nia Lailin Nisfah (Universitas Ahmad Dahlan, 2019)
The study aimed to find out the effect of assertive discipline on the children’s gadget addiction in a kindergarten in Semarang City. The present study was categorized into quantitative study. The population of the study was students and their parents in 2018/2019 academic year, there were 60 students and 60 parents, the samples were taken using purposive sampling technique. The data were collected using questionnaire filled by the parents. The analysis result found that the F value was 118,649 and Sig. = 0,000. Sig. value was lower than α = 0,05, meaning that H0 is rejected. It was found that assertive discipline significantly affects the early-aged children's gadget addiction. The study found that assertive discipline affects gadget addiction by 83.8%. While the other 16.2% was affected by other factors. It could be seen that assertive discipline possesses dominant effect on gadget addiction.